Real-Time Hand Motion Recognition: A Robust Low-Cost Approach - BAŞ, ANIL (My University, 2021)
This study presents a robust, low-cost hand motion recognition approach designed to run on low-end computer systems. Our method detects and tracks hand region using real-time images obtained from a low-resolution camera (i.e. webcam) and is not depended on any training or calibration and is not required any special camera apparatus or selectors. The proposed system involves several image processing techniques such as background subtraction, face detection, skin colour detection and template matching. The experimental results show promising performance under various conditions. The method has a wide range of applications where more natural ways of interaction required, such as virtual reality applications, assistive technologies and simulation.
Keywords: Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; Bilgisayar Bilimi Uygulamaları; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Computer Science Applications; Computer Science (miscellaneous); General Computer Science; Physical Sciences; Background subtraction; Face detection; Hand movement recognition; Motion tracking; Template matching